QSAR Applications on Polycyclic Aromatic Hydrocarbons and some derivatives - Andrada, Matias Fernando (2013)
Polycyclic Aromatic Hydrocarbons (PAHs) have been the focus of great attention for a long time owing to their impact on public health and the environment. In this article we overview various QSAR studies on PAHs and some derivatives, that have been developed during the last decade by different authors. Several properties of broad interest are analyzed, such as carcinogenesis, mutagenicity, biocatalytic oxidation, phototoxicity, dermal penetration, biodegradation, and others. The molecular descriptors types and modeling techniques used are briefly commented.